FINANCIAL PERFORMANCE ANALYSIS OF SOUTH SULAWESI - Mochamad Rizky Damara; Haliah Haliah; Andi Kusumawati (JIAR : Journal Of International Accounting Research, 2024)
The purpose of this study was to examine the financial performance of the local government of South Sulawesi Province in achieving good public financial management that can bring prosperity to the community. The analysis technique used is to calculate the degree of decentralization, the ratio of regional financial independence, efficiency, effectiveness, direct and indirect expenditure ratio, and growth ratio. The results of the analysis show that the ratio of the degree of decentralization is relatively stagnant from year to year with the ratio reaching 49%, indicating that the amount of local revenue is quite high compared to the total local revenue. The Regional Financial Independence Ratio shows that the government's ability to self-finance government activities, develop ment and services to the 2016-2020 budget community has increased sufficiently, in 2020, the regional financial independence ratio still shows a consultative relationship pattern. The Regional Financial Effectiveness Ratio describes the local government's ability to realize the planned local revenue with the target set based on the real potential of the region, in the last five years, obtained an average ratio value of 94.25%, meaning that the PAD target set can be realized optimally and the Efficiency Ratio shows that is efficient.